2020
DOI: 10.1029/2020gl090332
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Brown Carbon in the United States: Implications for Direct Radiative Effects

Abstract: A newly developed data set from the Interagency Monitoring of PROtected Visual Environments (IMPROVE) observation network, combined with a 3-D chemical transport model, is used to evaluate the spatial and temporal variability of brown carbon (BrC) in the United States. The model with BrC emitted from biomass burning and biofuel emissions agrees with the seasonal and spatial variability of BrC planetary boundary layer (PBL) absorption aerosol optical depth (AAOD) observations within a factor of 2. The model wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 92 publications
2
6
0
Order By: Relevance
“…Overall, a conclusion of this study was that the majority of the initial BrC was chemically unstable, with indications of a small (≈10%) absorption signal after a day or two of atmospheric processing. This one-day whitening time scale is consistent with modeling studies of both aircraft and aerosol optical depth data, such as from the IMPROVE network. …”
Section: Connections To the Atmospheresupporting
confidence: 83%
See 2 more Smart Citations
“…Overall, a conclusion of this study was that the majority of the initial BrC was chemically unstable, with indications of a small (≈10%) absorption signal after a day or two of atmospheric processing. This one-day whitening time scale is consistent with modeling studies of both aircraft and aerosol optical depth data, such as from the IMPROVE network. …”
Section: Connections To the Atmospheresupporting
confidence: 83%
“…This one-day whitening timescale is consistent with modeling studies of both aircraft and aerosol optical depth data, such as from the IMPROVE network. [286][287][288] Comparing Figures 14 and 15, this bleaching behavior in BrC emitted from forest fires is most consistent with that demonstrated by heterogeneous OH oxidation and direct photobleaching. However, the photobleaching modeled in Figure 14 simulates in-cloud conditions, which were not present during the measurements made in Figure 15, and direct photobleaching of non-aqueous BrC may not occur as rapidly (discussed in Section 4.1).…”
Section: Heterogeneous No 3 Oxidation Of Particulate Brcsupporting
confidence: 72%
See 1 more Smart Citation
“…Perspectives. This paper presents the first regional brownness map that will allow for ground-truthing model simulations or satellite retrievals of spectral aerosol light absorption (e.g., June et al 85 ). BC along with two classes of organic aerosol (i.e., BrC and WtC) with specific optical properties appear to explain the aerosol light absorption across the United States, while summertime atmospheric aging effectively converts BrC to WtC, thus reducing the brownness.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They found that best model-measurement agreement was achieved by accounting for both BrC absorption and photobleaching. Similarly, June et al 37 found that ignoring photobleaching in a global chemical transport model led to overestimating aerosol absorption compared to Interagency Monitoring of Protected Visual Environments (IMPROVE) observations. On the other hand, Brown et al 36 found that even though implementing BrC absorption in a global chemical transport model led to better agreement between model absorption Ångström exponent (AAE) values over biomass-burning regions and those retrieved from Aerosol Robotic Network (AERONET) observations, the model underestimated single scattering albedo (SSA) values over these regions compared to AERONET.…”
Section: Introductionmentioning
confidence: 99%